Good feasibility of the new German blood donor questionnaire - Houareau, Claudia; Stötzer, Frank (Transfusion medicine and hemotherapy, 2017)
Background: We assessed the effect of the uniform donor questionnaire (UDQ) on deferral rates in first-time and repeat donors. We focused on the introduced question about unprotected sexual contact with a new partner. Another goal was a stratified comparison of the deferral rates of the donor questionnaire (DQ) and UDQ. Methods: Data on donors and deferrals using the DQ and UDQ were collected at four blood establishments. The comparison included a 2-year period by questionnaire version. For the comparison of the questionnaires, an adjusted multinomial logistic regression was performed. Results: The analysis included 260,848 donations. First-time (FTD) and repeat donations (RD) showed higher deferral rates with the UDQ (FTD +5.4%, RD +1.4%). Deferral due to a new partner was 3.0% in first-time and 0.4% in repeat donors. The majority of these occurred in the youngest age groups. The most frequent deferral criterion was ‘disease' (5.1%). Conclusion: The regression revealed stronger predictors for deferral than the questionnaire version. Especially younger age carried a higher and independent risk for deferral. The additional deferrals of mainly young first-time donors due to a new sexual partner may identify those donors with potential heterosexual risk behavior who would otherwise not be identified.